2011
DOI: 10.1016/j.jcrs.2010.12.050
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous bilateral cataract surgery: Economic analysis; Helsinki Simultaneous Bilateral Cataract Surgery Study Report 2

Abstract: No author has a financial or proprietary interest in any material or method mentioned.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
73
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(76 citation statements)
references
References 14 publications
1
73
0
1
Order By: Relevance
“…Previous studies 1,[6][7][8][9][10][11][12] have demonstrated that ISCS is equally safe and efficacious compared with DSCS. This US-based cost-minimization analysis found that ISCS resulted in significant cost reductions compared with DSCS from the payer and patient perspectives.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies 1,[6][7][8][9][10][11][12] have demonstrated that ISCS is equally safe and efficacious compared with DSCS. This US-based cost-minimization analysis found that ISCS resulted in significant cost reductions compared with DSCS from the payer and patient perspectives.…”
Section: Discussionmentioning
confidence: 99%
“…An economic analysis in Finland found that surgical outcomes and patient satisfaction were similar in ISCS and DSCS groups and noted that "[b]ecause of equal effectiveness, the cost-effectiveness analysis turned into a cost analysis." 12(p1005) Few economic studies [12][13][14] have compared ISCS with DSCS, and no US-based analyses were found to date. The international data used hospital cost models, and this article tried to fill in the gaps by considering the payer, patient, and societal perspectives in the United States.…”
mentioning
confidence: 99%
“…From this they calculated that the cost to prevent SBE would be €739 million, or about $1 billion per SBE case prevented. 11 It is important to note that this does not prevent bilateral infection at that rate, which remains a mathematical risk, it only prevents the two infections from candidates for ISBCS, voluntarily choose it over DSBCS, when allowed to choose freely. 12 This is almost exactly the same percentage I experience…”
Section: Money and Isbcsmentioning
confidence: 99%
“…This is not only more convenient for the patient, but also more cost-effective and eases the demand on support infrastructure for mobilityrestricted patients [5] [6]. With an aging population these considerations will be of increased importance, particularly in an era where health care is obliged to focus on cost efficiency.…”
Section: Introductionmentioning
confidence: 99%